Performance evaluation of axial-loaded circular steel tubes strengthened by welding under service load. (15th November 2022) - Zhao, Xianzhong; Lyu, Jiafeng; Yan, Shen; Chen, Xiaoming; Wu, Xiaofeng; Xu, Xiaoming; Gao, Feng
Highlights: Three welding schemes are examined for strengthening circular steel tubes. The effects of service load, welding scheme and gaps are revealed. Welding-induced deformation and stress re-distribution are evaluated. Thermal-mechanical FE models prove effective to reproduce the tests. Abstract: This paper investigates the strengthening by welding method for axial-loaded circular steel tubes under service load, with a particular focus on the effects of service load and welding scheme. One un-strengthened member and four strengthened members were tested; the varying parameters included three welding schemes and two service load levels. Complementary coupled thermal–mechanical finite-element (FE) models and pure mechanical FE models accounting for no welding process were developed; only the former can faithfully reproduce the full-range behavior of the strengthened member. From the tests and FE parametric studies, the major conclusions included: (1) Notable axial shortening and deflection were observed during strengthening, reflected by obvious plateaus on the deformation curves; (2) Compared to continuous welding which led to the largest axial shortening and lateral fluctuation, intermittent welding and hybrid welding effectively reduced the welding-induced deformation and therefore are better choices; (3) Welding generated a field of intense tensile stress in and around the welds, and correspondingly, between the welds existed the compression zone; the compressive stress in the original member was larger than that in the strengthening member, and could also reach yield strength under high service load; (4) Welding-induced deformation increased with the service load level, with the dependence of the axial shortening being largely linear while that of the deflection being nonlinear; the ultimate resistance decreased with the increasing service load level; (5) The asymmetric gap pattern has a noteworthy effect on the performance of the strengthened member, primarily resulting from the asymmetric welding heat input.